PHANGS-ML: the universal relation between PAH band and optical line-ratios across nearby star-forming galaxies - Baron, Dalya; Sandstrom, Karin M.; Sutter, Jessica; Hassani, Hamid; Groves, Brent; Leroy, Adam K.; Schinnerer, Eva; Boquien, Médéric; Brazzini, Matilde; Chastenet, Jérémy; Dale, Daniel A.; Egorov, Oleg; et al. (The astrophysical journal, 2025)
The structure and chemistry of the dusty interstellar medium (ISM) are shaped by complex processes that depend on the local radiation field, gas composition, and dust grain properties. Of particular importance are polycyclic aromatic hydrocarbons (PAHs), which emit strong vibrational bands in the mid-infrared, and play a key role in the ISM energy balance. We recently identified global correlations between PAH band and optical line ratios across three nearby galaxies, suggesting a connection between PAH heating and gas ionization throughout the ISM. In this work, we perform a census of the PAH heating–gas ionization connection using ∼700,000 independent pixels that probe scales of 40–150 pc in 19 nearby star-forming galaxies from the PHANGS survey. We find a universal relation between logPAH(11.3 μm/7.7 μm) and log([S II]/Hα) with a slope of ∼0.2 and a scatter of ∼0.025 dex. The only exception is a group of anomalous pixels that show unusually high (11.3 μm/7.7 μm) PAH ratios in regions with old stellar populations and high starlight-to-dust emission ratios. Their mid-infrared spectra resemble those of elliptical galaxies. Active galactic nucleus hosts show modestly steeper slopes, with a ∼10% increase in PAH(11.3 μm/7.7 μm) in the diffuse gas on kiloparsec scales. This universal relation implies an emerging simplicity in the complex ISM, with a sequence that is driven by a single varying property: the spectral shape of the interstellar radiation field. This suggests that other properties, such as gas-phase abundances, gas ionization parameter, and grain charge distribution, are relatively uniform in all but specific cases.